Organized interests and trilogues in a post-regulatory era of EU policy-making. Issue 1 (2nd January 2021) - Greenwood, Justin; Roederer-Rynning, Christilla
ABSTRACT: Organized interests and trilogues are permanent features of the everyday policy-making of the EU, but little is known about their interaction. Can organized interests access this secluded and informal arena of EU decision making? If so, what implications does their degree of access have? Are there different patterns of interaction between different types of organized interests and the different co-decision making institutions? How do posited asymmetries between business interests and other types of civil society interests, manifest themselves when it comes to trilogues? As much as organized interests lobbying institutions, do we also find evidence of the reverse as a pathway seeking to influence trilogue negotiations? In this article we conceptualise rilogues as informal institutions delivering political choices, distinguishing between different periods of trilogue informality, and flesh out an ideal-type of contemporary trilogues as 'complementary informal institutions' in a 'post-regulatory' state. We pinpoint valuable as well as enduringly problematic features of trilogue informality and permeability. Based on a substantial recent interview survey among 100 trilogue 'insiders' and 'outsiders', we provide evidence of extensive ties between these players, their implications for the democratic quality of EU legislation. We develop further research questions surrounding the relationship between organized interests and trilogues.